Mycosis fungoides in a 12-year-old boy. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
Mycosis fungoides is the most frequent – more than 50% of cases – among primary cutaneous lymphomas and represents 60% (1) of T-cell forms (CTCL). It usually affects the adult, on average towards the end of the 6th decade of life. However, it can also affect children and adolescents (2). In children as in adults, the male gender prevails and the initial lesions appear in unexposed locations. Differential diagnosis in children must be made with numerous other conditions, from atopic dermatitis to superficial scleroderma, annular lichenoid dermatitis of youth and leprosy. The prognosis of mycosis fungoides arising in the prepubertal age is not different from that of the adult. The 10-year survival rate for patients with limited skin forms in patches or plaques is 98% and patients with a few, not infilted patches have a life expectancy practically equal to that of a control population (2).